Islamic Moderation as A Resolution of Different Conflicts of Religion - Betria Zarpina Yanti; Doli Witro (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2020)
Some tragedies and humanitarian conflicts that are both heartbreaking and worrying have been taking place in different parts of Indonesia. The cause of the conflict can be political factors, economic disparity, cultural disparity, ethnic and religious sentiments. Thus, it becomes very urgent for groups that are easily exposed to the conflict to understand Islamic moderation as a conflict resolution of differences in religious beliefs. This research is library research with qualitative research methods and descriptive approaches. Analysis of the data on the subject uses an inductive approach with data sourced from books, journals, newspapers, and scientific papers that are related to the object being studied. The results showed that the current national problems such as economic inequality, cultural disparity, ethnic and religious sentiments as well as the threat of conflict could only be resolved through cooperation with the principle of mutual understanding among religious communities. Thus through moderation of Islamic plurality, diversity, or diversity that has become a necessity can be utilized as universal energy to break down the problems of the Indonesian nation today.